All this could be yours : a thriller [large type] - Ryan, Hank Phillippi (Center Point Large Print, 2026)
"Debut sensation Tessa Calloway is on a whirlwind book tour for her instant bestseller, All This Could Be Yours. In a different city every night, Tessa receives standing ovations from adoring fans while her husband Henry and their two children cheer her on from their brand-new dream house. But there's a chilling problem with Tessa's triumphant book tour--she soon discovers she is being stalked by someone who's obsessed not only with sabotaging her career, but also with destroying her perfect family back home. Tessa fears the fallout from an impossible decision she once made--what felt like a genuine deal with the devil--appears to be coming due. And she's realizing that every high-stakes bargain comes with a high-stakes price. If Tessa can't untangle who's threatening to expose her darkest secrets, she'll lose her career, her family--and possibly her life."--